Design and Dynamic Simulation Analysis of a Wheel–Track Composite Chassis Based on RecurDyn - Yaowei Li; Liguo Zang; Tuo Shi; Tian Lv; Fen Lin (World Electric Vehicle Journal, 2021)
The traditional chassis has the problems of low trafficability and poor stability under complex and changeable unstructured conditions. Thus, a wheel rail composite chassis is proposed. The chassis had a tracked travel mechanism at the front wheels and a wheeled travel mechanism at the rear wheels. This study presents the design, theoretical analysis and dynamic simulation analysis of the chassis. The maximum values of the passability of the wheel–track composite chassis that can be passed were calculated according to the relevant parameters. Furthermore, the chassis was modeled and simulated using RecurDyn to verify whether the values were reasonable. According to different values of the terrain, slope, vertical obstacle height and trench width, the change regularity of the track tension and driving torque of the chassis were obtained. The chassis is designed to improve the vehicle’s ability to operate under complex and diverse unstructured conditions.